HBR guide to being more productive (Boston, 2017)
Every day begins with the same challenge: too many tasks on your to-do list and not enough time to accomplish them. Perhaps you tell yourself to just buckle down and get it all done--skip lunch, work a longer day. Maybe you throw your hands up, recognize you can't do it all, and just begin fighting the biggest fire or greasing the squeakiest wheel. And yet you know how good it feels on those days when you're working at peak productivity, taking care of difficult and meaty projects while also knocking off the smaller tasks that have been hanging over your head forever. Those are the times when your day didn't run you--you ran your day. To have more of those days more often, you need to discover what works for you given your strengths, your preferences, and the things you must accomplish. Whether you're an assistant or the CEO, whether you've been in the workforce for 40 years or are just starting out, this guide will help you be more productive.
Keywords: Industrial productivity,Psychology, Industrial,Năng suất công nghiệp,Tâm lý, công nghiệp